The circulatory half-lives of α -profibrin and α-fibrin monomer, and comparisons with other fibrin(ogen) derivatives - Shainoff, John R.; DiBello, Patricia M. (Thrombosis and Haemostasis, 2003)
Previous studies showed that α-fibrin monomer (lacking both A-fibrinopeptides, FPA) is normally cleared from the circulation before it assembles into a clot. Recent studies indicate that substantial quantities of an intermediate, α-profibrin lacking only one of the two FPA are produced in the course of conversion of human fibrinogen to fibrin. Since clearance of the α-fibrin monomer is saturable and receptor mediated, the extent to which α-profibrin or other fibrin(ogen) derivatives might compete for monomer uptake was deemed important. We compared plasma decay of injected human α-fibrin, fibrinogen, and α-profibrin in rabbits using rabbit anti-human fibrinogen for assays. The circulatory half-life of human α-fibrin monomer was short (t1/2 = 2.3 h) and followed a simple exponential decay curve, as anticipated from clearance of rabbit α-fibrin. It was absorbed as fast as it permeated the extravascular space with no redistribution. Human fibrinogen had a long half-life (t1/2 = 39.5 h), calculated from the double exponential plasma decay curves (redistribution + catabolism) observed over 28 h. The α-profibrin had an intermediary half-life (t1/2 = 11 h) determined from double exponential decay curves. Since redistribution accompanied the slow clearance of α-profibrin, its binding by the fibrin receptor(s) must be weak, probably too weak to compete with the clearance of α-fibrin monomer. The initial production of α-fibrin monomer is only partially dependent on prior formation of α-profibrin, as recently shown. Thus, it is the slow clearance and the weak competition from α-profibrin that underlie the occurrence of substantial levels of α-profibrin unaccompanied by detectable levels of α-fibrin monomer in many subjects with vascular disease.
Keywords: Fibrinogen; α-profibrin; α-fibrin; clearance